2018
DOI: 10.22395/rium.v17n32a10
|View full text |Cite
|
Sign up to set email alerts
|

La transformada de Radon aplicada a la segmentación de imágenes digitales en escala de grises

Abstract: En este artículo de investigación científica se da a conocer a la comunidad interesada en el procesamiento digital de imágenes, una aplicación inédita de la transformada de Radon para segmentar imágenes en escala de grises, lo que permite la identificación y clasificación de regiones u objetos, misma que puede extenderse a imágenes en color. Los resultados obtenidos se compararon con los resultados de dos algoritmos clásicos de segmentación: el algoritmo de umbralización Otsu optimizado, y el algoritmo de crec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
(5 reference statements)
0
6
0
Order By: Relevance
“…In [15], the author identified that an effective solution for COVID- 19 has not yet been found and that only the recommendations of the authorities and health organizations should be followed, which are the use of masks, maintaining two meters of social distance, frequent hand washing, avoiding frequent mouth or nose contact. Of all these measures, social distancing is something that cannot be properly controlled, which is why it was proposed to implement a social distancing recognition system as a preventive measure for COVID-19 using Deep Learning.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In [15], the author identified that an effective solution for COVID- 19 has not yet been found and that only the recommendations of the authorities and health organizations should be followed, which are the use of masks, maintaining two meters of social distance, frequent hand washing, avoiding frequent mouth or nose contact. Of all these measures, social distancing is something that cannot be properly controlled, which is why it was proposed to implement a social distancing recognition system as a preventive measure for COVID-19 using Deep Learning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In 8-bit images, there can be up to 256 shades of gray. Each pixel in a grayscale image has a brightness value between 0 (black) and 255 (white) [19]. Another is "binarization", it converts the digital image into a black and white image, in such a way that the essential properties of the image are preserved.…”
Section: Matlabmentioning
confidence: 99%
See 1 more Smart Citation
“…In 8-bit images, there can be up to 256 shades of gray. Each pixel in a grayscale image has a brightness value between 0 (black) and 255 (white) [22]. Another is "binarization", it converts the digital image into a black and white image, in such a way that the essential properties of the image are preserved.…”
Section: E Matlabmentioning
confidence: 99%
“…Another is "pixel mapping", it records an arbitrary number of moving images with respect to the fixed image (reference) [24]. Another is "subtraction of images", it subtracts each element of the matrix from the corresponding element of the matrix and returns the difference in the corresponding element of the output matrix [22].…”
Section: E Matlabmentioning
confidence: 99%